If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73 + -4x = 41x + 23 Reorder the terms: 73 + -4x = 23 + 41x Solving 73 + -4x = 23 + 41x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-41x' to each side of the equation. 73 + -4x + -41x = 23 + 41x + -41x Combine like terms: -4x + -41x = -45x 73 + -45x = 23 + 41x + -41x Combine like terms: 41x + -41x = 0 73 + -45x = 23 + 0 73 + -45x = 23 Add '-73' to each side of the equation. 73 + -73 + -45x = 23 + -73 Combine like terms: 73 + -73 = 0 0 + -45x = 23 + -73 -45x = 23 + -73 Combine like terms: 23 + -73 = -50 -45x = -50 Divide each side by '-45'. x = 1.111111111 Simplifying x = 1.111111111
| 4(n+(n+4))=3(n+2)+5 | | 2x-3+5x-1+8x+19=180 | | 15.55=4.95 | | x=3+0,5x | | 8x-95=3x-10 | | x=2+0,5x | | -14=6+4w | | 25/36-3/15= | | 3v+8=-13 | | 3(x-1)-11=7 | | x=5+0,5x | | 139-7x=20x+19 | | x^3+x^2-3x+8=9 | | 39=5u-16 | | 10-8x=50-36x | | x+0,5x=x | | 7x+32=2x+12 | | 6n+6-9=6n | | 4x^4+25x^2-160=0 | | 0=(x+7)*(2X+3) | | 162-6x=4+22 | | 0=2x-70 | | -6w+3(w+2)=-18 | | 6x-9=21-3 | | 3(x-5)+14=2(x+1) | | 3x-10=3x+4 | | 2(x-5)-10=x+7 | | 10y+6=5y-19 | | 2(x+3)-18=0 | | 7a+8b=15ab | | 3-1(2x+8)=-(3x-2) | | 7y-4=3y+8 |